Factors affecting Y-Balance Test in elite adolescent soccer players - Lee, J.-B.; Jeon, J.-Y.; Ju, S.-k.; Park, K.-J. (Trends in Sport Sciences, 2025)
Introduction: The ability of soccer players to maintain dynamic balance is crucial for their performance in physical tasks and matches. Therefore, it is essential to examine the factors influencing the dynamic balance of these players.